Enhancing Students' Inferential Reading Skills through a Higher Order Thinking Skills Based Module: An Experimental Study - Wahyuni Fitria; Nafiah, Uyun (Yayasan Nurul Yakin Bunga Tanjung, 2025)
Limited empirical research has examined how Higher-Order Thinking Skills (HOTS)-based instructional modules can enhance inferential reading among Indonesian English as a Foreign Language (EFL) learners in Islamic higher education. Addressing this gap, this quasi-experimental study evaluated the impact of a HOTS-based module grounded in Bloom’s Revised Taxonomy on students’ inferential reading skills and metacognitive strategies. A total of 57 EFL learners from an Islamic university in Indonesia participated (28 experimental, 29 control) over a six-week intervention. Inferential reading performance was measured using a validated multiple-choice reading comprehension test. Data were analyzed using paired and independent samples t-tests with effect size estimation. The experimental group demonstrated significant improvement (mean gain = 10.89 points; p = 0.000; Cohen’s d = 1.22), and a significant difference was found between groups (p = 0.008; Cohen’s d = 0.75), indicating a strong practical impact. This quasi-experiment provides evidence-based support for integrating HOTS-oriented instruction to foster 21st-century skills such as critical literacy and metacognitive awareness in Indonesian EFL contexts. The findings support the integration of HOTS (Higher Order Thinking Skills) modules into teacher certification programs and EFL teacher training curricula within Islamic higher education institutions across Southeast Asia, contributing to the advancement of pedagogical practices and teacher professional development,